THE RESULTS DIFFERENCE BETWEEN INITIAL AND FINAL MEASUREMENT IN 500-METER CROSS-COUNTRY RACE WITH DIFFERENT TRAINING METHODS - Rade Stefanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
the difference between initial and final measurement